The RNA-methyltransferase Misu (NSun2) poises epidermal stem cells to differentiate. - Sandra Blanco; Agata Kurowski; Jennifer Nichols; Fiona M Watt; Salvador Aznar Benitah; Michaela Frye (PLoS Genetics)
Homeostasis of most adult tissues is maintained by balancing stem cell self-renewal and differentiation, but whether post-transcriptional mechanisms can regulate this process is unknown. Here, we identify that an RNA methyltransferase (Misu/Nsun2) is required to balance stem cell self-renewal and differentiation in skin. In the epidermis, this methyltransferase is found in a defined sub-population of hair follicle stem cells poised to undergo lineage commitment, and its depletion results in enhanced quiescence and aberrant stem cell differentiation. Our results reveal that post-transcriptional RNA methylation can play a previously unappreciated role in controlling stem cell fate.